Antimeiotic Properties of the Aqueous Extracts of Leaves, Fruits and Roots of the Muskmelon Cucumis melo L. (Cucurbitaceae) in the Pest Grasshopper Zonocerus variegatus L. (Pyrgomorphidae) (Global Journal of Science Frontier Research, 2022)
The Muskmelon Cucumis melo L is a Cucurbitaceae widely cultivated in Cameroon for its nutritional and ethnomedicinal benefits Species of Cucurbitaceae are known to contain several bioactive molecules that include the terpenoid cucurbitacins which has been shown to cause significant molting defects and mortality in a variety of Coleoptera insect species such as Leperesinus fraxini PANZ Coleoptera Scolytidae Stereonychus fraxini DE GEER Coleoptera Curculionidae This study was designed to determine if an aqueous extract of Muskmelon C melo var Cantaloupensis Americana could profoundly affect the meiotic process in the Orthoptera grasshopper Zonocerus variegatus a veritable food crop pest in Africa south of the Sahara Different concentrations 0 g ml 5 g ml 10 g ml 20 g ml 30 g ml and 40 g ml of aqueous extract of the leaves fruits and roots of C melo were respectively injected using the intraperitoneal method into the hemocoel of new reproductive and adult male individuals of Z variegatus Cytogenetic analysis revealed that Muskmelon extracts significantly reduced meiotic indexinduced meiotic chromosome abnormalities and significantly reduced chiasma frequency Chromosome abnormalities recorded included sticky chromosomes Anaphase 1bridges and laggards The 40 g ml extract of roots was the most cytotoxic and induced the production of ghost cells These results indicated that the aqueous extracts of C melo are potential meiotic regulators that can affect fertility in the pest species Z variegatus
Keywords: cytotoxicity; genotoxicity; cucumis melo L; aqueous extracts; meiotic process; meiotic index